Solutions manual to accompany Game theory : an introduction - Barron, E. N. (Emmanual N.), 1949- (J. Wiley & Sons, 2013)
This book provides detailed solutions and explanations to the problems presented in Game Theory: An Introduction, Second Edition. It is a trusted guide and an excellent resource for professors of mathematics and economics and researchers in economics, finance, engineering, operations research, statistics, and computer science.